The Eckert number phenomenon - an experimental investigation of the heat transfer from a rotating cylinder in a cross-flow - Gschwendtner, MA (Macmillan (India), 2006)
The Eckert number phenomenon describes a reversal in heat transfer from a moving wall at an Eckert number Ec ≈ 1. In this report the Eckert number phenomenon is confirmed experimentally for the first time. For that purpose the heat transfer from a heated, vertically rotating cylinder in a cross-flow was investigated where the cylinder surface represents a heat rejecting, moving wall. In order to perform the experiments in a range where the predicted phenomenon occurs, rotational speeds of up to 30,000 rpm were necessary which required the development of a contact-free heating concept and a new optical measuring technique suitable for boundary layers. The results show, among other things, that the temperature difference between the wall and the surrounding fluid has a significant effect on the predicted reversal of heat transfer at the wall. The impact of rotation on flow patterns, boundary layer behavior and heat transfer could be clearly identified. It appears that the velocity-ratio Ω acts like an independent parameter, in that flow patterns correspond to this dimensionless number. Furthermore, it seems that rotation dominates over cross-flow, both fluid-dynamically and thermally above Ω = 2.